The New Commonwealth. - Secara, Claudiu A. (Algora Pub., 2007)
Russia will compromise both modelsthe old communist orthodoxy and casino capitalismthen it can become the dominant power in a Eurasian commonwealth within a new world order quite different from what most Americans imagine." Booklist.